2014
DOI: 10.1155/2014/151724
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Methods of RNA Extraction from Formalin-Fixed Paraffin-Embedded Tissue Specimens

Abstract: The present study aimed to compare two different methods of extracting RNA from formalin-fixed paraffin-embedded (FFPE) specimens of diffuse large B-cell lymphoma (DLBCL). We further aimed to identify possible influences of variables—such as tissue size, duration of paraffin block storage, fixative type, primers used for cDNA synthesis, and endogenous genes tested—on the success of amplification from the samples. Both tested protocols used the same commercial kit for RNA extraction (the RecoverAll Total Nuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…Already in the 90s, Ben-Ezra et al showed that after six hours of tissue fixation by the Bouin solution, the PCR gave no result [16]. Later, this conclusion has been questioned by a team in Brazil [17] who showed with two different protocols that it was possible to get between 33.3% and 80% positivity to PCR despite the use of the Bouin solution. This same team demonstrated that formalin-fixed tissues gave PCR positivity rates between 87.5% and 100%; and the use of formaldehyde as a fixative gave between 17.6% and 73.7% of positivity.…”
Section: Discussionmentioning
confidence: 99%
“…Already in the 90s, Ben-Ezra et al showed that after six hours of tissue fixation by the Bouin solution, the PCR gave no result [16]. Later, this conclusion has been questioned by a team in Brazil [17] who showed with two different protocols that it was possible to get between 33.3% and 80% positivity to PCR despite the use of the Bouin solution. This same team demonstrated that formalin-fixed tissues gave PCR positivity rates between 87.5% and 100%; and the use of formaldehyde as a fixative gave between 17.6% and 73.7% of positivity.…”
Section: Discussionmentioning
confidence: 99%
“…None of the previous studies available in the literature described the possible factors that could influence the amplification success. Therefore, the current study made the option of investigating some of the potential interferences in the nucleic acid obtainment process, namely: tissue fragment size, blocks' storage time, used fixative type, different cDNA synthesis primers and different primer sequences, among others [18].…”
Section: Preparing Ffpe Tissue Sections For Nucleic Acids Extractionmentioning
confidence: 99%
“…It consisted of using 1 ml phosphate buffer saline (PBS) with 5 min incubation at room temperature, followed by full speed centrifugation for 5 min in the R-5418 microfuge (Eppendorf AG, Hamburg, Germany). This procedure is done to remove possible fixative residues that could work as PCR inhibitors [18]. Next, the same process was used in the DNA extraction performed by our team.…”
Section: Preparing Ffpe Tissue Sections For Nucleic Acids Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these unclassified variants, a percentage is predicted to affect splicing. Specific kits are available to isolate RNA from formalin-fixed paraffin-embedded (FFPE) tissue blocks, and previous studies show that PCR, RT-PCR and even next-generation sequencing (NGS) are possible on these RNA samples [12,13]. RNA analysis on RNA isolated from the FFPE tissue is currently not standardly performed but would enable the analysis of somatic splice site variants.…”
Section: Introductionmentioning
confidence: 99%